An assessment of floristic diversity of Gandhamardan Hill Range, Orissa, India - Reddy, C. Sudhakar; Pattanaik, Chiranjibi (Bangladesh Journal of Plant Taxonomy, 2009)
The plant resources of Gandhamardan hill range were studied and analysed. A total of 912 vascular species belonging to 556 genera under 142 families were recorded. Herbs dominate the flora followed by trees, climbers and shrubs. Dominance of phanerophytes indicates the tropical moist and humid climate. Proper conservation and management plans are needed to save the natural resources, especially medicinal plants, of this sacred hill range. Keywords: Floristic diversity; Gandhamardan hill range; Life-form; Medicinal plants; Orissa. DOI: 10.3329/bjpt.v16i1.2744 Bangladesh J. Plant Taxon. 16(1): 29-36, 2009 (June)